2015
DOI: 10.19027/jai.14.79-89
|View full text |Cite
|
Sign up to set email alerts
|

Combination of garlic - shatterstone herb powder to control Streptococcus agalactiae infection in tilapia

Abstract: <p class="NoParagraphStyle" align="center"><strong>ABSTRACT</strong><strong></strong></p><p class="NoParagraphStyle" align="center"><strong> </strong></p><p class="NoParagraphStyle">This study was aimed at determining potential of combination powder of garlic <em>Allium sativum</em>-shatterstone herb <em>Phyllanthus niruri</em> supplemented in feed against <em>S. agalactiae</em> infection in tilapia. Four conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This condition was presented on the increased blood hematological profiles in fish fed with the treatment feed, mainly on 14 days of rearing period. This discovery was similar to the previous study that reported an increased health status of Nile tilapia after feeding with meniran and garlic supplemented feed (Fauziah et al, 2015). Erythrocyte is one of blood components functioned as an oxygen transporter.…”
Section: Discussionsupporting
confidence: 91%
“…This condition was presented on the increased blood hematological profiles in fish fed with the treatment feed, mainly on 14 days of rearing period. This discovery was similar to the previous study that reported an increased health status of Nile tilapia after feeding with meniran and garlic supplemented feed (Fauziah et al, 2015). Erythrocyte is one of blood components functioned as an oxygen transporter.…”
Section: Discussionsupporting
confidence: 91%
“…Garlic is sliced thinly and then dried in the oven at 60°C until dry. After that, the garlic is blended until it forms a powder, then sieved with a 75 µm (Fauziah et al, 2015).…”
Section: Making Garlic Powder (Allium Sativum)mentioning
confidence: 99%
“…In the context of aquaculture, the use of garlic has been shown to stimulate growth, boost the immune system, and encourage feeding responses in fish. This effect is associated with the content of organosulfur compounds, especially allicin, which is found in garlic (Fauziah & Wahjuningrum, 2015).…”
Section: Introductionmentioning
confidence: 99%